0689 Sedative and Stimulant Misuse and Suicide Ideation in a Community Sample. (25th May 2022) - Bobadilla, Vanessa; Fernandez, Fabian-Xosé; Tubbs, Andrew; Chakravorty, Subhajit; Perlis, Michael; Hale, Lauren; Branas, Charles; Killgore, William; Wills, Chloe; Grandner, Michael
Abstract: Introduction: Previous studies have shown that prescription sleep medications are associated with suicide ideation. In this study we seek to identify the risk of off-label or illicit use of sedatives/hypnotics to predict suicidal ideation. Methods: Data were from the Sleep and Healthy Activity, Diet, Environment, and Socialization (SHADES) Study, including N=1, 003 working-age adults. For the present study, the data on off-label or illicit stimulants and sedatives were examined. Suicide ideation was assessed by whether participant reported any ideation in the past 2 weeks (PHQ, Item #9). Covariates included age, sex, education, race/ethnicity, and smoking. Additional models included adjustment for insomnia severity (ISI), daytime sleepiness (ESS), sleep duration (NHANES), psychiatric health (PHQ4), and general stress (PSS). Results: In adjusted models examining sedatives/hypnotic use, higher likelihood of suicidal ideation was associated with any use (OR=1.77, 95%CI[1.26, 2.47]), recent use (OR=2.71, 95%CI[1.77, 4.15]), desire to use (OR=2.14, 95%CI[2.74, 6.26]), problematic use (OR=7.39, 95%CI[3.32, 16.47]), role limitations (OR=7.94, 95%CI[3.39, 18.59]), others expressing concern (OR=4.38, 95%CI([2.29, 8.41]), and inability to control use (OR=7.15, 95%CI[3.60, 14.20]). Similarly, models examining stimulant use showed that higher likelihood of suicide ideation was associated with history of use (OR=1.81, 95%CI[2.01, 3.93]), recent use (OR=4.44, 95%CI[2.63, 7.49]), desire to use (4.82, 95%CI[2.78, 8.34]), problematic use (OR=17.04, 95%CI[5.67, 51.24]), role limitations (OR=9.07, 95%CI[3.47, 23.68]), others expressing concern (OR=17.26, 95%CI([7.48, 39.84]), and inability to control use (OR=6.44, 95%CI[3.26, 12.71]). When sleep and mental health variables were added to the model, results were attenuated but remained significant at the p<.05 level. Conclusion: Illicit use of substances that both promote sleep or arousal are associated with suicidal ideation, over and above contributions of sleep disturbance and mood/stress. It is possible that these behaviors represent self-medication attempts or an adverse effect of these drugs. Further research on these problematic associations is recommended. Support (If Any):